2014
DOI: 10.1016/j.rgmx.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Calcio sérico total y calcio corregido como predictores de severidad en pancreatitis aguda

Abstract: TC and ACC, measured within the first 24hours, are useful severity predictors in acute pancreatitis, with sensitivity and predictive values comparable or superior to those of the conventional prognostic scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(33 reference statements)
1
5
1
Order By: Relevance
“…Similarly, when ACC of 7.72 mg/dl was computed as cutoff for severe AP, we found sensitivity of 88%, specificity of 69.1%, PPV of 56.4%, and NPV of 92.7%. When 7.5 mg/dl is taken as a cutoff value for albumin-corrected calcium in our study, the sensitivity and negative predictive values decreased up to 80% and 89.1%, respectively, and while comparing the sensitivity, specificity, and predictive values of ACC with that of the study done by Gutierrez-Jimenez et al [ 5 ], our sensitivity was much higher (88% versus 67%) and a positive predictive value (56.4% versus 40%) was obtained when the cutoff value was taken as 7.72 mg/dl. As explained above, the higher sensitivity and PPV could be due to the higher cutoff value in our study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Similarly, when ACC of 7.72 mg/dl was computed as cutoff for severe AP, we found sensitivity of 88%, specificity of 69.1%, PPV of 56.4%, and NPV of 92.7%. When 7.5 mg/dl is taken as a cutoff value for albumin-corrected calcium in our study, the sensitivity and negative predictive values decreased up to 80% and 89.1%, respectively, and while comparing the sensitivity, specificity, and predictive values of ACC with that of the study done by Gutierrez-Jimenez et al [ 5 ], our sensitivity was much higher (88% versus 67%) and a positive predictive value (56.4% versus 40%) was obtained when the cutoff value was taken as 7.72 mg/dl. As explained above, the higher sensitivity and PPV could be due to the higher cutoff value in our study.…”
Section: Discussionsupporting
confidence: 51%
“…It has been evaluated as a mortality prognostic factor and has also been evaluated as a predictor of severe AP with infection. Albumin-corrected calcium has also been associated with severity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total calcium and corrected calcium have shown similar efficacy like that of Ranson and APACHE II score in prediction of SAP. In a prospective study of 96 patients, Gutiérrez-Jiménez et al have found sensitivity, specificity, positive predictive value, and negative predictive value of 67%, 82%, 27%, and 96% at a maximum cut-off level of 7.5 mg/dL for total calcium and 67%, 90%, 40%, and 96% for corrected calcium with a maximum cut-off level of 7.5 mg/dL [ 104 ].…”
Section: Emerging Potential Biomarkers For Prediction Of Severity mentioning
confidence: 99%
“…MM score was also recently used to determine AP severity [ 3 ]. Other single serum markers of AP severity have been extensively studied, such as hematocrit, creatinine, BUN, TSC, lactate and CRP [ 4 , 7 , 21 23 ]. In addition, some serum pro- and anti-inflammatory markers have been proved to be associated with AP severity, such as interleukin-6, interlekin-8, interleukin-10 and tumor necrosis factor alpha; and serum procalcitonin, a reliable marker of infection/sepsis and useful for predicting infected necrosis in AP.…”
Section: Discussionmentioning
confidence: 99%